2020
DOI: 10.1186/s43044-020-00121-w
|View full text |Cite|
|
Sign up to set email alerts
|

Association of culprit lesion plaque characteristics with flow restoration post-fibrinolysis in ST-segment elevation myocardial infarction: an intravascular ultrasound-virtual histology study

Abstract: Background Not every patient achieves normal coronary flow following fibrinolysis in STEMI (ST-segment elevation myocardial infarction). The culprit lesion plaque characteristics play a prominent role in the coronary flow before and during percutaneous coronary intervention. The main purpose was to determine the culprit lesion plaque features by virtual histology-intravascular ultrasound (VH-IVUS) in patients with STEMI following fibrinolysis in relation to baseline coronary angiogram TIMI (thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…DCM is a serious complication of diabetes[ 37 ] that is characterized by irreversible damage to myocardial structure and function in diabetic patients, due to hyperglycemia and metabolic disorders[ 38 ]. In terms of pathogenesis, studies have shown that DCM is an independent and specific myocardial injury, and the pathogenesis of DCM is different from that of hypertensive heart disease, coronary atherosclerotic heart disease, and other heart diseases[ 39 , 40 ]. Our present study suggests that HG levels might activate inflammatory pathways, to induce apoptosis and fibrous tissue proliferation in diabetic patients, thus playing an important role[ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…DCM is a serious complication of diabetes[ 37 ] that is characterized by irreversible damage to myocardial structure and function in diabetic patients, due to hyperglycemia and metabolic disorders[ 38 ]. In terms of pathogenesis, studies have shown that DCM is an independent and specific myocardial injury, and the pathogenesis of DCM is different from that of hypertensive heart disease, coronary atherosclerotic heart disease, and other heart diseases[ 39 , 40 ]. Our present study suggests that HG levels might activate inflammatory pathways, to induce apoptosis and fibrous tissue proliferation in diabetic patients, thus playing an important role[ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified an error in the labelling of Figs. 1 and 2 .…”
mentioning
confidence: 99%